Chemical characterization and antioxidant capacity of the araçá-pera (Psidium acutangulum): An exotic Amazon fruit. (September 2015) - Ramos, Andrezza S.; Souza, Rodrigo O.S.; Boleti, Ana Paula de A.; Bruginski, Estevan R.D.; Lima, Emerson S.; Campos, Francinete R.; Machado, Marcos B.
Abstract: The "araçá-pera" ( Psidium acutangulum DC) is an exotic guava consumed by the Brazilian Amazon population. This paper describes 22 compounds from this fruit by UHPLC–HRMS and NMR methods, being one disaccharide, five monosaccharides, two organic acids, one trihydroxycinnamic acid glucopyranosyl, one tannine digalloyl glucopyranosyl, five triterpenoid acids, and six fatty acids. It also quantifies the level of ascorbic acid (AA) by HPLC–MS (74.32 ± 1.23 mg/100 g of fresh fruit), and defines the chemical antioxidant activities by DPPH and ABTS + assays (24.96 ± 0.75, 90.57 ± 0.63 mg of vitamin C/100 g fresh fruit, respectively), and a cell-based assays (76–100%). These results have shown that this exotic guava can be consumed as a nutraceutical ingredient, as well as be used in the production of functional foods in the Amazonian diet to prevent chronic and oxidative diseases. Highlights: Quantification of ascorbic acid in Psidium spp. fruits by HPLC–MS Determination of antioxidant potential from exotic fruits of Psidium spp. We reported the chemical constituents from Psidium acutangulum fruit by UHPLC–HRMS. Increasing information about their fruits will reveal the nutritional potential.